Usefulness of the AHEAD score for prediction of all-cause death in patients with acute and chronic coronary syndromes - Shunsuke Tamaki; Akinori Higaki; Hiroshi Kawakami; Kazuhisa Nishimura; Katsuji Inoue; Shuntaro Ikeda; Osamu Yamaguchi; Naoyuki Akashi; Tetsuya Matoba; Takahide Kohro; Tomoyuki Kabutoya; Kazuomi Kario; et al. (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: The AHEAD (A: atrial fibrillation; H: hemoglobin; E: elderly; A: abnormal renal parameters; D: diabetes mellitus) score was developed to predict all-cause death (ACD) in patients with heart failure. However, its predictive value for ACD compared to the CHADS2 score in patients with coronary artery disease (CAD) remains unknown. Methods: This retrospective multicenter cohort study analyzed data of the patients who underwent percutaneous coronary intervention for acute (ACS) or chronic coronary syndromes (CCS) using the Clinical Deep Data Accumulation System (CLIDAS) database. The AHEAD score was calculated by assigning 1 point each for atrial fibrillation, anemia, age >70 years, elevated creatinine levels (>130 μmol/L), and diabetes mellitus. Results: In total, 9033 patients were enrolled between April 2013 and March 2019. Cox multivariate analysis revealed that both the AHEAD and CHADS2 scores were independently associated with ACD in patients with ACS and CCS (hazard ratio [HR], 1.91 [95 % CI, 1.70–2.14] for ACS and 1.72 [1.54–1.92] for CCS, and HR 1.17 [1.06–1.29] for ACS and 1.18 [1.08–1.29] for CCS, respectively). However, receiver operating characteristic curve analysis demonstrated that the AHEAD score had a significantly higher predictive value for ACD compared to the CHADS2 score in both ACS and CCS. A significant difference was found in the rate of ACD among patients stratified by the AHEAD score in both groups. Conclusions: The AHEAD score demonstrated superior predictive value for ACD compared to the CHADS2 score in patients with CAD, regardless of whether they had ACS or CCS.